The Social and Environmental Risk of Commercialization Cultural Tourism Using Instagram In Indonesia - Pramanti, Adilita (Department of Sociology, Universitas Nasional (Indonesia), 2020)
The purpose of this research to describe social risks to the development of society in the current digital technology trap. This research is useful to develop the role of sociology research in the dynamic development of digital society in Indonesia. Culture becomes an economic asset in the digital market. The needs and tastes of social media users are now the capital of the digital market to develop the potential of cultural tourism from every culinary beauty or specialty in Indonesia.In 2019, Instagram users in Indonesia reached 22.6 percent with the business promotion category reaching almost 52 percent more than using personal accounts. Photos and locations that are tourist destinations uploaded to Instagram and attract interest and make it easier for other users to find these tourist locations. Not infrequently a place where there had never been tourists became crowded and viral because of promotions on Instagram. This study describes the forms of environmental and social risk from the use of Instagram for the commercialization of cultural tourism in Indonesia. The research method is a qualitative descriptive study of literature and content analysis of 100 Instagram accounts that actively aim at promoting cultural tourism in Indonesia. Keywords: Social Risk, Environment, Commercialization, Tourism, Instagram